In vitro determination of biocompatibility of different grafts/implants used for reconstructive surgery of tendon - GOSWAMI, T K; KUMAR, NAVEEN; GUPTA, O P; SHARMA, A K; PAWDE, A M (The Indian Journal of Animal Sciences, 2014)
Seven grafts/implants, viz.1% and 2% glutaraldehyde preserved tendon allowgrafts, plasma preserved and normal saline frozen tendon allografts, acellular allografts, human hair andÂ  carbon fibres were used for in vitro cell cytotoxicity in PBMC culture, cell cytotoxicity in MDBK cell lines and immunocompatility test. None of the sample showed any significant cytotoxicity even at 1:20 concentration.